Paper roughness measurement using airborne ultrasound - Stor-Pellinen, Jyrki; Luukkala, Mauri (Sensors and actuators. A. Physical., 1995)
Paper roughness has been studied using high-frequency airborne ultrasound. The measurement principle is based on the attenuation that occurs when ultrasound is reflected from a rough surface. Paper samples have been tested and results compared with data from conventional air-leak measurements. The proposed method is non-contacting and it allows the possibility of developing fast and rugged applications for the laboratory or for on-location product testing.